Daca x - 4/3 = 1, (3), atunci x =
Răspunsuri la întrebare
Răspuns de
8
x-4/3=1,(3)
x-4/3=(13-1)/9
x-4/3=12/9
x-4/3=4/3
x=4/3+4/3=8/3
x-4/3=(13-1)/9
x-4/3=12/9
x-4/3=4/3
x=4/3+4/3=8/3
petrutdelia:
Multumesc
Răspuns de
4
x-4/3=1,(3)
x-4/3=13-1/9
x-4/3=12/9
x-4/3=4/3
x=4/3+4/3
x=4/3*2
x=8/3
x-4/3=13-1/9
x-4/3=12/9
x-4/3=4/3
x=4/3+4/3
x=4/3*2
x=8/3
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă